An Optogenetic Tool for Induced Protein Stabilization Based on the Phaeodactylum tricornutum Aureochrome 1a Light–Oxygen–Voltage Domain. Issue 7 (27th March 2020) - Hepp, Sebastian; Trauth, Jonathan; Hasenjäger, Sophia; Bezold, Filipp; Essen, Lars-Oliver; Taxis, Christof
Abstract: Control of cellular events by optogenetic tools is a powerful approach to manipulate cellular functions in a minimally invasive manner. A common problem posed by the application of optogenetic tools is to tune the activity range to be physiologically relevant. Here, we characterized a photoreceptor of the light–oxygen–voltage (LOV) domain family of Phaeodactylum tricornutum aureochrome 1a (AuLOV) as a tool for increasing protein stability under blue light conditions in budding yeast. Structural studies of AuLOV wt, the variants AuLOV M254, and AuLOV W349 revealed alternative dimer association modes for the dark state, which differ from previously reported AuLOV dark-state structures. Rational design of AuLOV-dimer interface mutations resulted in an optimized optogenetic tool that we fused to the photoactivatable adenylyl cyclase from Beggiatoa sp. This synergistic light-regulation approach using two photoreceptors resulted in an optimized, photoactivatable adenylyl cyclase with a cyclic adenosine monophosphate production activity that matches the physiological range of Saccharomyces cerevisiae . Overall, we enlarged the optogenetic toolbox for yeast and demonstrated the importance of fine-tuning the optogenetic tool activity for successful application in cells. Graphical abstract: Image 1 Highlights: Light-induced protein stabilization. Alternative dark state dimer structures of Phaeodactylum tricornutum aureochrome 1a. Rational engineering of AuLOV dimerization. Photoactivatable adenylyl cyclase from Beggiatoa sp. engineered for budding yeast. Physiological relevant regulation of cAMP production in Saccharomyces cerevisae .